Survival costs of reproduction predict age-dependent variation in maternal investment. - Kindsvater, H; Bonsall, M; Alonzo, S (2011)
Life-history theory predicts that older females will increase reproductive effort through increased fecundity. Unless offspring survival is density dependent or female size constrains offspring size, theory does not predict variation in offspring size. However, empirical data suggest that females of differing age or condition produce offspring of different sizes. We used a dynamic state-variable model to determine when variable offspring sizes can be explained by an interaction between female age, female state and survival costs of reproduction. We found that when costs depend on fecundity, young females with surplus state increase offspring size and reduce number to minimize fitness penalties. When costs depend on total reproductive effort, only older females increase offspring size. Young females produce small offspring, because decreasing offspring size is less expensive than number, as fitness from offspring investment is nonlinear. Finally, allocation patterns are relatively stable when older females are better at acquiring food and are therefore in better condition. Our approach revealed an interaction between female state, age and survival costs, providing a novel explanation for observed variation in reproductive traits.